Furfural tolerance of mutant Saccharomyces cerevisiae selected via ionizing radiation combined with adaptive laboratory evolution - Junle Ren; Miaomiao Zhang; Xiaopeng Guo; Xiang Zhou; Nan Ding; Cairong Lei; Chenglin Jia; Yajuan Wang; Jingru Zhao; Ziyi Dong; Dong Lu (Biotechnology for Biofuels and Bioproducts, 2024)
Abstract Background Lignocellulose is a renewable and sustainable resource used to produce second-generation biofuel ethanol to cope with the resource and energy crisis. Furfural is the most toxic inhibitor of Saccharomyces cerevisiae cells produced during lignocellulose treatment, and can reduce the ability of S. cerevisiae to utilize lignocellulose, resulting in low bioethanol yield. In this study, multiple rounds of progressive ionizing radiation was combined with adaptive laboratory evolution to improve the furfural tolerance of S. cerevisiae and increase the yield of ethanol. Results In this study, the strategy of multiple rounds of progressive X-ray radiation combined with adaptive laboratory evolution significantly improved the furfural tolerance of brewing yeast. After four rounds of experiments, four mutant strains resistant to high concentrations of furfural were obtained (SCF-R1, SCF-R2, SCF-R3, and SCF-R4), with furfural tolerance concentrations of 4.0, 4.2, 4.4, and 4.5 g/L, respectively. Among them, the mutant strain SCF-R4 obtained in the fourth round of radiation had a cellular malondialdehyde content of 49.11 nmol/mg after 3 h of furfural stress, a weakening trend in mitochondrial membrane potential collapse, a decrease in accumulated reactive oxygen species, and a cell death rate of 12.60%, showing better cell membrane integrity, stable mitochondrial function, and an improved ability to limit reactive oxygen species production compared to the other mutant strains and the wild-type strain. In a fermentation medium containing 3.5 g/L furfural, the growth lag phase of the SCF-R4 mutant strain was shortened, and its growth ability significantly improved. After 96 h of fermentation, the ethanol production of the mutant strain SCF-R4 was 1.86 times that of the wild-type, indicating that with an increase in the number of irradiation rounds, the furfural tolerance of the mutant strain SCF-R4 was effectively enhanced. In addition, through genome-transcriptome analysis, potential sites related to furfural detoxification were identified, including GAL7, MAE1, PDC6, HXT1, AUS1, and TPK3. Conclusions These results indicate that multiple rounds of progressive X-ray radiation combined with adaptive laboratory evolution is an effective mutagenic strategy for obtaining furfural-tolerant mutants and that it has the potential to tap genes related to the furfural detoxification mechanism. Graphical Abstract